Tecnologias para os serviços públicos - Macaya, Javiera Fernanda Medina; Ribeiro, Manuella Maia; Lima, Camila dos Reis; Dhaou, Soumaya Ben; Isagah, Tupokigwe; Magalhães, Larissa (São Paulo, 2025)
34 p.